2004
DOI: 10.1227/01.neu.0000130444.71677.bc
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Aqueductoplasty and Interventriculostomy for the Treatment of Isolated Fourth Ventricle in Children

Abstract: The significant failure rate of fourth ventricle shunts has led to the development of alternative treatment methods. Endoscopic aqueductoplasty or interventriculostomy presents an effective, minimally invasive, and safe procedure for the treatment of isolated fourth ventricle in pediatric patients. Compared with suboccipital craniotomy and microsurgical fenestration, endoscopic aqueductoplasty is less invasive, and compared with fourth ventricle shunts, it is more reliable and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 13 publications
0
48
0
Order By: Relevance
“…Recent series of endoscopic treatment for TFV suggest a success rate of 25% to 33% over 9.8 to 29.7 months with aqueductoplasty alone, but as high as 71% to 100% when aqueductoplasty or interventriculostomy was followed by fourth ventricular stenting. 4,11,30 Ogiwara and Morota studied 8 pediatric patients who underwent endoscopic stent placement for TFV (n = 5) or pre-TFV (aqueduct still patent) (n = 3). They found that all patients experienced improvement in symptoms and reduction in fourth ventricular size with reoperation in 33% of patients over a mean follow-up of 49.6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Recent series of endoscopic treatment for TFV suggest a success rate of 25% to 33% over 9.8 to 29.7 months with aqueductoplasty alone, but as high as 71% to 100% when aqueductoplasty or interventriculostomy was followed by fourth ventricular stenting. 4,11,30 Ogiwara and Morota studied 8 pediatric patients who underwent endoscopic stent placement for TFV (n = 5) or pre-TFV (aqueduct still patent) (n = 3). They found that all patients experienced improvement in symptoms and reduction in fourth ventricular size with reoperation in 33% of patients over a mean follow-up of 49.6 months.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an internal CSF diversion channel for trapped fourth ventricle may be achieved with aqueductoplasty, with or without aqueductal stent placement, or by fenestration of the superior medullary velum. 3,6,7,20,22,24 This procedure is not devoid of complications; it carries a risk of midbrain injury, with neurological defects such as dysconjugate eye movement and Parinaud syndrome. It may be performed by approaching the aqueduct from above, when the supratentorial ventricles are dilated, or from below with a suboccipital approach, usually when a working CSF shunting device is present.…”
Section: Discussionmentioning
confidence: 99%
“…Shunting of the fourth ventricle has long been advocated as the procedure of choice; 4,7,8 however, this procedure has a high rate of associated shunt malfunction, requiring revision in up to 40% of patients within the first year, 9 and significant complications have been described. 1,10-13 Endoscopic approaches have been utilised: aqueductoplasty, aqueductal stent placement, lateral ventricle fenestration, [14][15][16][17][18] and third ventriculostomy. 19 There are, however, high rates of failure and significant complications 17 21 The dura was closed with a dural graft.…”
Section: Discussionmentioning
confidence: 99%